Higher percentage of CD133+ cells is associated with poor prognosis in colon carcinoma patients with stage IIIB - Li, Chun-Yan; Li, Bao-Xiu; Liang, Yi; Peng, Rui-Qing; Ding, Ya; Xu, Da-Zhi; Zhang, Xin; Pan, Zhi-Zhong; Wan, De-Sen; Zeng, Yi-Xin; Zhu, Xiao-Feng; Zhang, Xiao-Shi (Journal of translational medicine, 2009)
Background Cancer stem cell model suggested that tumor progression is driven by the overpopulation of cancer stem cells and eradicating or inhibiting the symmetric division of cancer stem cells would become the most important therapeutic strategy. However, clinical evidence for this hypothesis is still scarce. To evaluate the overpopulation hypothesis of cancer stem cells the association of percentage of CD133 + tumor cells with clinicopathological parameters in colon cancer was investigated since CD133 is a putative cancer stem cell marker shared by multiple solid tumors. Patients and methods Tumor tissues matched with adjacent normal tissues were collected from 104 stage IIIB colon cancer patients who were subject to radical resection between January, 1999 to July, 2003 in this center. The CD133 expression was examined with immunohistochemical staining. The correlation of the percentage of CD133 + cell with clinicopathological parameters and patients' 5-year survival was analyzed. Results The CD133 + cells were infrequent and heterogeneous distribution in the cancer tissue. Staining of CD133 was localized not only on the glandular-luminal surface of cancer cells but also on the invasive budding and the poorly differentiated tumors with ductal structures. Both univariate and multivariate survival analysis revealed that the percentage of CD133 + cancer cells and the invasive depth of tumor were independently prognostic. The patients with a lower percentage of CD133 + cancer cells (less than 5%) were strongly associated with a higher 5-year survival rate than those with a higher percentage of CD133 + cancer cells (greater than or equal to 55%). Additionally, no correlation was obtained between the percentage of CD133 + cancer cells and the other clinicopathological parameters including gender, age, site of primary mass, pathologic types, grades, and invasive depth. Conclusion The fact that a higher percentage CD133 + cells were strongly associated with a poorer prognosis in patients with locally advanced colon cancer implicated that CD133 + cancer cells contribute to the tumor progression, and the overpopulation hypothesis of cancer stem cell seems reasonable.